2016
DOI: 10.1007/s40261-016-0421-z
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionality Analysis for the Assessment of Abuse and Dependence Potential of Pregabalin in the French Pharmacovigilance Database

Abstract: The first cases of pregabalin-related abuse or dependence reported in France occurred later than in other European countries, since none had been described before 2010. This analysis in the FPVD did not find a higher proportion of abuse/dependence with pregabalin in comparison with other drugs. Considering evidence of pregabalin abuse worldwide, this analysis underlines the limitations of spontaneous reporting system in the field of addictovigilance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 30 publications
1
23
0
4
Order By: Relevance
“…First, there was no certainty that the reported event was actually due to the drug because confounding by concomitant medications and comorbidities is likely. Second, it is possible that the data involve a reporting bias, including the underreporting of adverse events, which is an inherent limitation of a voluntary reporting system like JADER and other pharmacovigilance databases …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, there was no certainty that the reported event was actually due to the drug because confounding by concomitant medications and comorbidities is likely. Second, it is possible that the data involve a reporting bias, including the underreporting of adverse events, which is an inherent limitation of a voluntary reporting system like JADER and other pharmacovigilance databases …”
Section: Discussionmentioning
confidence: 99%
“…Second, it is possible that the data involve a reporting bias, including the underreporting of adverse events, which is an inherent limitation of a voluntary reporting system like JADER 22 and other pharmacovigilance databases. 23,24…”
Section: Discussionmentioning
confidence: 99%
“…Pregabalin as a medication can cause dependence, which on some occasions can lead to abuse [20]. Norgaard et al, reported a 38 year-old man who was abusing pregabalin by self-administering 8.4 g of pregabalin daily and after 36 h of pregabalin discontinuation, he reported auditory hallucinations and suicidal ideation with associated sweating and tachycardia.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Opiate users prescribed gabapentin reportedly had a higher risk of opiate-related mortality compared to those not prescribed gabapentin. 43 In one pharmacovigilance database review, the incidence of pregabalin dependence per new prescription was lower than that of the benzodiazepine clonazepam, 44 which is a Schedule IV controlled substance in the United States (indicating greater abuse potential than Schedule V). In a laboratory study of a small number of non-drug-abusing volunteers, daily administration of therapeutic doses of pregabalin did not produce subjective effects suggesting abuse liability.…”
Section: Abuse Liability and Safetymentioning
confidence: 99%